LABOUR RIGHTS AND THE CANADA/COLOMBIA FTA: A FUNDAMENTALLY FLAWED CULTURE - Cardinal, Pierre-Alexandre (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2013)
From talks around the issue of the Generalized System of Preferences and more recent talks on bilateral and multilateral FTAs, the linkage between the promotion of universal labour rights and trade has been on the agenda of policy makers, and integrated into most FTAs. In the case of the recent Canada-Colombia Free Trade Agreement (CCFTA), Canadian officials negotiated the inclusion of a side agreement on labour cooperation (ALC) in order to deepen ties between the two countries, and support Colombian workers, who face severe repression by government and paramilitary forces. The current essay will bring forward and deepen the critiques formulated by civil society actors against CCFTA, and argue that the guarantees given by the agreement and the ALC are fundamentally flawed using an examination of the underlying meaning of the words of the agreement. By taking a structural approach, it will be argued that the general culture and habitus developed through the interests and usage of symbolic capital of structural actors have a central effect on the FTA and its ALC by completely altering the meaning of their language. Such a critique offers a relevant standpoint in the context of the on-going discussions revolving around the Trans-Pacific Partnership, and the general expansion of global integration through FTAs.